Chromebook for dummies ebook - Gregory, Peter H. (2020)
Get the most out of your Google Chromebook Chromebook For Dummies walks you through setting up your Chromebook, transitioning from traditional computers, customizing a Chromebook to fit your needs, navigating the many apps and their uses, and applying advanced settings and features. This book documents the features of all Chromebooks, approaching them from the point of view of a smart person who is intimidated by the technology. Offers extensive and practical information Covers all portable computers powered by Chrome OS Helps make it easy to drive these fast, user-friendly devices Includes coverage of the latest features in the Chrome operating system  You'll end up keeping this book close at hand, referring to it often as you explore the features of your Chromebook.